Expanding workers’ education in Nigeria within the context of EFA: the study circles option (2010)
The world is moving to a point where every country begins to realise that where the right to education is guaranteed, people have a greater chance to enjoy other rights. The UNESCO and most national governments, across the world, now realise that education offers an answer to many of the world’s problems. Thus, the aim of extending basic education to all; particularly the working adults with the context of Education for All (EFA becomes highly imperative. Given this background, this paper is out to examine the EFA goals (Goals 3, 4 and 6) as they relate to workers education in Nigeria. This is with the hope of achieving 50% improvement in adult literacy as well as meeting the qualitative learning needs of young and adults who constitute the active labour force of the country by 2015. However, it is the hope of the authors that equality of qualitative workers education opportunity by 2015 may be achieved most readily when the study circle culture is adopted. This will help provide conditions which enable each working class citizen to develop to his or her potentials within a group dynamics. The use of study circle will help to ensure that today’s organisations are turned into learning organisations where learning is not left to chance. Invariably the adoption of study circle by organisations in Nigeria, as suggested by the authors, would help to expand workers’ education and obviously will contribute significantly to organisational changes. Therefore, it is the opinion of the authors that the study circle culture should be built into the psyche of an average Nigerian to ensure a sustained voice in governance at all level of our natural life